2001
DOI: 10.1038/sj.jea.7500141
|View full text |Cite
|
Sign up to set email alerts
|

Childhood respiratory symptoms, hospital admissions, and long-term exposure to airborne particulate matter

Abstract: The effects of long -term exposure to air pollution on respiratory symptoms and respiratory hospitalization ( for asthma, bronchitis or pneumonia ) were assessed in a cross -sectional study of children ( ages 7 ± 11 years, N = 667 ) living in a moderately industrialized city in Central Slovakia. Individual health, residence and family history data obtained through the CESAR study were coupled, using Geographic Information System ( GIS ) technologies, with total suspended particulate ( TSP ) exposure estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 10 publications
1
32
0
2
Order By: Relevance
“…The early Harvard Six Cities Study found that a number of respiratory morbidity outcomes in schoolchildren (cough or persistent cough, bronchitis, chest illness, wheeze, and/or lower respiratory illness index) were positively associated with ambient particulate (measured as TSP) levels (16,22). A more recent Slovakian study has also found that the prevalence of respiratory nonasthmatic symptoms and hospitalizations was associated with increased TSP (17).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The early Harvard Six Cities Study found that a number of respiratory morbidity outcomes in schoolchildren (cough or persistent cough, bronchitis, chest illness, wheeze, and/or lower respiratory illness index) were positively associated with ambient particulate (measured as TSP) levels (16,22). A more recent Slovakian study has also found that the prevalence of respiratory nonasthmatic symptoms and hospitalizations was associated with increased TSP (17).…”
Section: Resultsmentioning
confidence: 93%
“…The prevalence of persistent cough in children reported in the three North American studies was 3-9% (11,12,14); in the Switzerland study it was 4.7-19.2% (13); and in the Slovakian study it was 24.9% (17). The prevalence of persistent phlegm in children reported in one of the three North American studies was 1-5% (12) and in the Slovakian study was 5.1% (17). The prevalence of bronchitis and the prevalence of persistent cough in children appeared to be markedly higher in the Chinese and Slovakian cities where ambient pollution levels were also higher.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a population of approximately 13,000 residents living in the Sasova complex, a suburban residential area of 15-story apartment blocks about 3 km away from the city center and 250 m higher in elevation. Major industries include a large wood processing facility near the city center and a cement plant located 5 km from the city center (Hruba et al, 2000 ) . Local heating sources rely primarily on natural gas.…”
Section: Introductionmentioning
confidence: 99%